Bridging the gap in full immunisation coverage with parental awareness and attitudes: a community-based cross-sectional analysis on routine childhood vaccinations in Perambalur district of Tamil Nadu, South India - Krishnapillai Vijayakumar; Vijay Anand; Neeraj Vinod Mohandas; Avani Dinesh; Vinod Mohandas; Sanidhya S Karve (BMJ Open)
Objectives To determine the independent predictors of full immunisation coverage (FIC) among children aged 12–23 months along with the parental awareness and attitudes (of children aged ≤23 months) regarding routine childhood vaccinations in Perambalur district of Tamil Nadu, South India.Design A community-based cross-sectional analysis.Setting Perambalur district situated in the central region of Tamil Nadu state, South India.Participants Parents of children aged ≤23 months.Outcome measures The primary outcome measured was the FIC and FIC plus in the district along with the parental awareness and attitudes regarding routine childhood vaccinations. The independent predictors of FIC and FIC plus were determined using multivariable logistic regression models.Results The study included 652 children, with a mean (±SD) age of 16.47 (±6.37) months and a male-to-female ratio of 60:40. The FIC and FIC plus of children aged 12–23 months were 91.3% (95% CI 88.64 to 93.33) and 79.7% (95% CI 76.15 to 82.80), respectively. The immunisation card retention was 97.9% among the parents of children aged 12–23 months. The independent predictors of FIC included below poverty line families (adjusted OR (AOR) 0.11; 95% CI 0.02 to 0.64), illiteracy among mothers (AOR 0.67; 95% CI 0.32 to 0.87), lack of immunisation card (AOR 0.14; 95% CI 0.03 to 0.55), lack of frequent home visits by healthcare worker (AOR 0.38; 95% CI 0.18 to 0.79) and hesitancy of parents towards vaccination (AOR 0.26; 95% CI 0.12 to 0.87).Conclusion This study revealed a high FIC in this specific district. However, achieving full coverage is influenced by factors like socioeconomic status, maternal education and parental attitudes. Understanding these factors is essential for improving immunisation rates and ensuring all children are protected.